European Global Cities in the Recent Economic Crisis. (September 2014) - Musil, Robert
Abstract Macroeconomic imbalances are a substantial characteristic of the recent economic crisis in Europe. As several authors emphasise the impact of the state, public institutions and territorial structures on the world city, the impact of the crisis on the economic performance of global cities becomes a crucial question. After discussing the theoretical aspects of the state – global city linkages and discussing two fields of influence on the global city formation, the empirical section analyses the deviation of national and regional growth performance to estimate the decoupling of European global cities from the national economies. The results show that the correlation between European global cities and the national scale also depends on the form of capitalism and the territorial organisation of statehood.